Mechanisms of microbial movement in subsurface materials. - Reynolds, P J (1989)
The biological factors important in the penetration of Escherichia coli through anaerobic, nutrient-saturated, Ottawa sand-packed cores were studied under static conditions. In cores saturated with galactose-peptone medium, motile strains of E. coli penetrated four times faster than mutants defective only in flagellar synthesis. Motile, nonchemotactic mutants penetrated the cores faster than did the chemotactic parental strain. This, plus the fact that a chemotactic galactose mutant penetrated cores saturated with peptone medium at the same rate with or without a galactose gradient, indicates that chemotaxis may not be required for bacterial penetration through unconsolidated porous media. The effect of gas production on bacterial penetration was studied by using motile and nonmotile E. coli strains together with their respective isogenic non-gas-producing mutants. No differences were observed between the penetration rates of the two motile strains through cores saturated with peptone medium with or without galactose. However, penetration of both nonmotile strains was detected only with galactose. The nonmotile, gas-producing strain penetrated cores saturated with galactose-peptone medium five to six times faster than did the nonmotile, non-gas-producing mutant, which indicates that gas production is an important mechanism for the movement of nonmotile bacteria through unconsolidated porous media. For motile strains, the penetration rate decreased with increasing galactose concentrations in the core and with decreasing inoculum sizes. Also, motile strains with the faster growth rates had faster penetration rates. These results imply that, for motile bacteria, the penetration rate is regulated by the in situ bacterial growth rate.(ABSTRACT TRUNCATED AT 250 WORDS)